Ascribing and limiting fiduciary obligations: Understanding the operation of consent - Getzler, J (Oxford University Press, 2014)
It is now a common observation that fiduciary duties typically arise from consent, express or implied, and regularly operate to prohibit certain behaviours in order to improve standards of positive conduct. These claims are each entirely valid, but consent is not a universal or complete explanations of the genesis of fiduciary duties, their content, and the proper remedies for breach. This essay makes a tentative start in applying the techniques of ascription and defeasibility to fiduciary law, arguing that consent plays a role in both creation and limitation of fiduciary obligations, but that consent interacts with an array of further mandatory and default terms to control entry into, variation and exemption, and exit from fiduciary relationships. The chapter surveys current law, and concludes that not “who is a fiduciary,” or “what is a fiduciary duty,” but “how are fiduciary duties changed” is now the compelling question.